2020
DOI: 10.20944/preprints202002.0061.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Learning Based Drug Screening for Novel Coronavirus 2019-nCov

Abstract: A novel coronavirus called 2019-nCoV was recently found in Wuhan, Hubei Province of China, and now is spreading across China and other parts of the world. 2019-nCoV spreads more rapidly than SARS-CoV. Unfortunately, there is no drug to combat the virus. It is of high significance to develop a drug that can combat the virus effectively before the situation gets worse. It usually takes a much longer time to develop a drug using traditional methods. For 2019-nCoV, it is now better to rely on some alternative meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…However, previously reported docking (virtual screening) campaigns with Mpro targets were able to process only few millions or even thousands compounds. [6,[28][29][30] The main reason for that is that conventional docking is too computationally expensive and slow, while the libraries of available chemicals are growing exponentially. [31] To address this general challenge, we have recently developed a novel deep learning-based approach for accelerated screening of large chemical libraries, consisting of billions of entities.…”
Section: Introductionmentioning
confidence: 99%
“…However, previously reported docking (virtual screening) campaigns with Mpro targets were able to process only few millions or even thousands compounds. [6,[28][29][30] The main reason for that is that conventional docking is too computationally expensive and slow, while the libraries of available chemicals are growing exponentially. [31] To address this general challenge, we have recently developed a novel deep learning-based approach for accelerated screening of large chemical libraries, consisting of billions of entities.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, a deep-learning-based approach was investigated by Zhang et al for screening available drugs for effective treatment of COVID-19. 96 In this model (DFCNN), RNA sequences were collected from the GISAID database to explore related 3D protein sequences modeling using homology modeling. The DFCNN explores possible protein–ligand interactions of high accuracy to perform drug screening without using docking or molecular dynamics.…”
Section: Artificial Intelligence-assisted Approaches For Covid-19 Panmentioning
confidence: 99%
“…This protease-based modeling successfully identified 4 chemical compound databases and confirmed that peptides-based drugs exhibited good stability, the desired bioavailability, and negligible immune responses. 96 …”
Section: Artificial Intelligence-assisted Approaches For Covid-19 Panmentioning
confidence: 99%
“…In the space of a few weeks after the acknowledgement of the latest coronavirus outbreak, several laboratories started to deposit homology models for the main viral protease [42,43], and then for all the SARS-CoV-2 proteins using the server I-TASSER [44]. Others performed docking in these models [45] or developed their own models to understand how the virus enters cells by modeling the Spike (S) protein and human angiotensin-converting enzyme 2 (ACE2) protein interaction [46]. At the time of writing there were structures available for the SARS-CoV-2 main protease in complex with an inhibitor N3 (PDB ID 6LU7) [47] and S1 and S2 subunits of Spike glycoprotein receptor-binding domain up (6VSB), the post fusion core subunit (6LXT) and the HR2 domain (6LVN) [48,49].…”
Section: Sars-cov-2 Drug Discovery Effortsmentioning
confidence: 99%